Effectiveness of Health Education with Booklet and Poster Method on Improving Knowledge and Attitude About 1000 HPK Among Primigravida Mothers in North Tapanuli District - Janner Pelanjani Simamora; Dimpu Rismawaty Nainggolan (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
One of the efforts to change the knowledge and attitude of mothers towards 1000 HPK is to provide health education. Media is very essential in the successful delivery of messages. In choosing a good media, it is very helpful to successfully convey the message, otherwise the media that is not appropriate can result in the delivery of a bad message. One of the media used is booklet and poster media. The purpose of this study was to analyse the Effectiveness of Health Education with Booklet Method and Poster Method on Improving Knowledge and Attitude of Primigravida Mothers about 1000 HPK in North Tapanuli Regency in 2024. The research used is quantitative with a Quasi Experiment approach using a pre test and post test nonequivalent control group approach. Data analysis method is univariate analysis aimed at obtaining the frequency distribution of knowledge and attitudes studied and presented with a percentage. Bivariate data analysis aims to see the effectiveness of the independent variable with the dependent variable. Due to the normal distribution of data in this Peneltian, the research analysis used the independent Sample T Test which aims to see the difference between the booklet method and the poster method. Sampling in this study with Purposive Sampling technique as many as 16 samples on the booklet method and 16 samples on the poster method. The study used the T test and obtained p value for knowledge of 0.729 and for attitudes of 0.381 which means that the booklet method and poster are equally effective of primigravida about 1000 HPK at Siborong-borong, Pangaribuan, Sipahutar and Siatas Barita Community Health Centre. Keyword: Booklet, Poster, Knowledge, Attitude, 1000 HPK